Multiplicity-dependent production of Σ(1385)± and Ξ(1530)0 in pp collisions at √s = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Nath, Abhishek; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Journal of high energy physics, 2024)
The production yields of the Σ(1385)± and Ξ(1530)0 resonances are measured in pp collisions at $$ \sqrt{s} $$= 13 TeV with ALICE. The measurements are performed as a function of the charged-particle multiplicity ⟨dNch/dη⟩, which is related to the energy density produced in the collision. The results include transverse momentum (pT) distributions, pT-integrated yields, mean transverse momenta of Σ(1385)± and Ξ(1530)0, as well as ratios of the pT-integrated resonance yields relative to yields of other hadron species. The Σ(1385)±/π± and Ξ(1530)0/π± yield ratios are consistent with the trend of the enhancement of strangeness production from low to high multiplicity pp collisions, which was previously observed for strange and multi-strange baryons. The yield ratio between the measured resonances and the long-lived baryons with the same strangeness content exhibits a hint of a mild increasing trend at low multiplicity, despite too large uncertainties to exclude the flat behaviour. The results are compared with predictions from models such as EPOS-LHC and PYTHIA 8 with Rope shoving. The latter provides the best description of the multiplicity dependence of the Σ(1385)± and Ξ(1530)0 production in pp collisions at $$ \sqrt{s} $$= 13 TeV.
Im Titel sind ± und 0 hochgestellt
Gesehen am 05.05.2025
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Bórquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, A. Yüncü, F. Zanone, [und 1027 weitere]